2000
DOI: 10.1128/mcb.20.20.7784-7797.2000
|View full text |Cite
|
Sign up to set email alerts
|

Mmf1p, a Novel Yeast Mitochondrial Protein Conserved throughout Evolution and Involved in Maintenance of the Mitochondrial Genome

Abstract: A novel protein family (p14.5, or YERO57c/YJGFc) highly conserved throughout evolution has recently been identified. The biological role of these proteins is not yet well characterized. Two members of the p14.5 family are present in the yeast Saccharomyces cerevisiae. In this study, we have characterized some of the biological functions of the two yeast proteins. Mmf1p is a mitochondrial matrix factor, and homologous Mmf1p factor (Hmf1p) copurifies with the soluble cytoplasmic fraction. ⌬mmf1 cells lose mitoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
81
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(84 citation statements)
references
References 29 publications
2
81
0
Order By: Relevance
“…First, the inhibition was titratable and declined with decreasing protein concentration. Second, the data suggested that YjgF had a catalytic role in the assay because 1 M protein reduced PRA formation by ϳ300 M. Significantly, the human homolog (UK114) was active in this assay, consistent with the finding that UK114 complemented the yjgF mutant phenotypes in S. enterica 4 and Saccharomyces cerevisiae (34) in vivo. Together, these results emphasized that this protein family is characterized both by high sequence identity and functional conservation.…”
Section: Discussionsupporting
confidence: 74%
“…First, the inhibition was titratable and declined with decreasing protein concentration. Second, the data suggested that YjgF had a catalytic role in the assay because 1 M protein reduced PRA formation by ϳ300 M. Significantly, the human homolog (UK114) was active in this assay, consistent with the finding that UK114 complemented the yjgF mutant phenotypes in S. enterica 4 and Saccharomyces cerevisiae (34) in vivo. Together, these results emphasized that this protein family is characterized both by high sequence identity and functional conservation.…”
Section: Discussionsupporting
confidence: 74%
“…In particular, we observed the depletion of two proteins, MMF1 and Ilv5p (Fig. 2), which are necessary for mitochondrial DNA stability and mitochondrial functionality (32,33). A recent transcriptome analysis of cdc48 S565G cells demonstrated nuclear genes coding for mitochondrial proteins to be the largest group of differentially regulated genes (45).…”
Section: Mitochondria Are Crucially Impaired In Apoptotic Cdc48mentioning
confidence: 98%
“…2B, panel 1) and ketol acid reductoisomerase (Ilv5p, Table 1), two mitochondrial proteins fundamental for the stability of mitochondrial DNA (32,33), suggest reduced mitochondrial functionality upon CDC48 mutation. We found depletion of mitochondrial cyclophilin C (Fig.…”
Section: Mitochondria In Cdc48 S565g Cells Are Enlarged Compared Withmentioning
confidence: 99%
“…Members of this protein family share extensive similarities and have been implicated in diverse cellular processes in a number of organisms (17,24,28,39,40,46,47,50,67). Though no in vitro activity has been described, in the annotation of various genomes more than 10 different functions have been attributed to members of this family (http://e2f.umbi.umd .edu).…”
mentioning
confidence: 99%